(untitled) (International journal of artificial intelligence, 2026)
This article explores the concept, content, and structural components of the national innovation system. The national innovation system is considered a complex socio-economic mechanism that ensures scientific and technological development, integrating processes of innovation creation, implementation, and dissemination. The study analyzes the structural elements of the national innovation system, including research institutions, educational establishments, producers, government agencies, and innovation infrastructure, examining their interconnections and effectiveness. Additionally, the article highlights strategic directions for the development of the national innovation system and its impact on economic growth, competitiveness, and social progress.